2021
DOI: 10.1038/s41598-021-92879-5
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-1246 in extracellular vesicles secreted from metastatic tumor induces drug resistance in tumor endothelial cells

Abstract: Tumor endothelial cells (TECs) reportedly exhibit altered phenotypes. We have demonstrated that TECs acquire drug resistance with the upregulation of P-glycoprotein (P-gp, ABCB1), contrary to traditional assumptions. Furthermore, P-gp expression was higher in TECs of highly metastatic tumors than in those of low metastatic tumors. However, the detailed mechanism of differential P-gp expression in TECs remains unclear. miRNA was identified in highly metastatic tumor extracellular vesicles (EVs) and the roles of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…In particular, its upregulation has been associated with tumor growth, metastasis, and drug resistance in different types of cancer. 72 , 73 , 74 In breast cancer, exosomal miR-1246 has been used as diagnostic biomarker because of its high expression specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its upregulation has been associated with tumor growth, metastasis, and drug resistance in different types of cancer. 72 , 73 , 74 In breast cancer, exosomal miR-1246 has been used as diagnostic biomarker because of its high expression specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy triggers TECs to suppress IGFBP7, and the upregulation of IGF1 activates the FGF4-FGFR1-ETS2 pathway in TECs and accelerates the conversion of tumor cells to chemoresistant tumor stem-like cells (58). Tumorderived microvesicles induce EC drug resistance via IL-6 upregulation, suggesting tumor secreting factor cause resistance of TEC to chemotherapy (59). Kikuchi et al reported that IL-8, induced by anti-cancer drugs, increases the expression of p-glycoprotein/ABCB1, which is a drug transporter in TECs of human bladder cancers (60) (Figure 3).…”
Section: Drug Resistance In Tecsmentioning
confidence: 99%
“…In addition to the different origins of TECs, TEC phenotypes are affected by TME. Comparing the TECs stimulated by two different metastatic tumor supernatants, found that the treatment of highly metastatic tumor conditioned medium increased the resistance of TECs to 5-fluorouracil (5-FU) (68). After coculture with lung cancer cells, human umbilical vein ECs showed enhanced cell motility and microvascular formation and a decrease in the percentage of apoptosis (69).…”
Section: Heterogeneity Of Tumor-specific Endothelial Cellsmentioning
confidence: 99%